Aggregated Color Descriptors for Land Use Classification - V. Jovanović; V. Risojević (Telfor Journal, 2015)

(untitled)
In this paper we propose and evaluate aggregated color descriptors for land use classification in aerial images. First, global and local Bag-of-Colors (BoC) descriptors are evaluated for land use classification. Influence of different parameters on the performance and efficiency of classification were tested. A small modification in the process of computing of BoC is introduced, which improves the overall classification performance. We also present a new, very simple color descriptor, termed Vector of Locally Aggregated Colors (VLAC) which has as good classification results as the modified BoC, but using linear support vector machines.